CMCH and MORU: A Highly Successful Collaboration - Maude, Richard J; Yunus, Emran Bin; Hoque, Md Gofranul; Hassan, Md Mahtab Uddin; Hossain, Md Amir; Samad, Rasheda; Rahman, Ridwanur; Ghose, Aniruddha; Day, Nicholas P; White, Nicholas J; et al. (Journal of Chittagong Medical College Teachers’ Association, 2010)
DOI: 10.3329/jcmcta.v20i1.4926 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):2-5